Quidam [videorecording (DVD)] - Mallet, David (Director); Dragone, Franco (Columbia TriStar Home Video, 1999)
Cirque du Soleil takes its unique, award-winning show from under the big top and brings it into your home to enjoy forever! This collector's item features one of their most popular shows, Quidam, which was recorded live in Amsterdam. Known throughout the world as masters of awe inspiring performance art, Cirque du Soleil continues to thrill with the most amazing acrobatics ever seen!